Envisioning entrepreneurial engagement in North Korea - Kibler, E; Ginting-Szczesny, B; Vaara, E; Heikkilä, J-P (Academy of Management, 2021)
Entrepreneurship research has long been interested in the emergence of new business activities in various geographical and institutional contexts. However, these studies have largely focused on market and transition economies at the expense of planned economies. To address this limitation, our study focuses on an extreme case: how people envision their entrepreneurial engagement in North Korea. Drawing on prospective entrepreneurial narratives by North Korean university students, our empirical analysis identifies and elaborates four types of narratives envisioning entrepreneurial engagement: economic patriotism, industrious collectivism, individualistic heroism, and personal dreamwork. We show how types of prospective entrepreneurial engagement reflect different motivations and development goals, and how they align with, or deviate from, the dominant institutional discourse in a rigidly planned economy. In conclusion, we advance entrepreneurship research by introducing new ways of studying and theorising prospective entrepreneurial engagement under extreme institutional constraints.